Hodnocení vzniku dekubitů se zaměřením na hodnotící škály - Hujová, Aneta; Kopecký, Miroslav (Ošetřovatelské perspektivy, 2024)
Background: To reduce the prevalence of pressure ulcers, it is important to assess the risk of pressure ulcers in patients on an individual basis. Proper risk assessment requires consideration of all modifiable and non-modifiable risk factors and the use of an appropriate scale to determine the risk of pressure ulcers development. Aim: Based on the content of the retrieved studies, to create a review of scales for assessing the risk of pressure ulcers in patients hospitalized in standard ward departments. Methods: The search for specialized primary studies was conducted in licensed electronic databases such as PubMed, Scopus, Web of Science, and EBSCO Discovery Service. Based on their analysis, a review study was prepared, focusing on the assessment of the risk of pressure ulcers development according to individual scales. Results: Eighteen studies published in the English language were found. No studies were found in the Czech or Slovak languages. The retrieved studies used assessment scales to determine the risk of pressure ulcers development in patients. In most studies, the Braden Scale was predominantly utilized. Conclusion: The results indicate that the Braden Scale is most commonly used for evaluating the risk of pressure ulcers in patients hospitalized in ward departments.
Keywords: rizikové faktory; hospitalizace; Pressure Ulcer; Clinical Studies as Topic; Risk Factors; průzkumy a dotazníky; hodnocení rizik; podvýživa; Hospitalization; Malnutrition; klinická studie jako téma; Risk Assessment; dekubity; Surveys and Questionnaires